New record and dietary ecology of a poorly known amphibian species, Micryletta menglienica (Yang and Su, 1980), from Vietnam - Hai Ngoc Ngo; Anh Van Pham; Truong Nguyen; Nenh Ba Sung; Thuy Van Tran; Minh Duc Le; Anh Ngoc Thi Ho (Acta Herpetologica)
Recent field surveys revealed a new population of the Menglian Paddy Frog (Micryletta menglienica) from Son La Province, northwestern Vietnam based on molecular and morphological analyses. The species has been listed as "Data Deficient” in the IUCN Red List. To date, knowledge about the natural history of this species is scarce, including data on its dietary ecology. Using the stomach-flushing method, we analyzed stomach contents of 45 individuals (21 males and 24 females) from a total of 52 captured frogs because stomachs of six males and one female (13.5%) were empty. The food spectrum of M. menglienica comprises 12 types with a total of 691 prey items (687 invertebrate items and four unidentified items), belonging to six insect orders, larvae and Araneae. Similar to other species of the family Microhylidae, M. menglienica is also identified as an ant (Formicidae) – termite (Rhinotermitidae) eating specialist with distinctly higher percentages of occurrence frequency (F = 65 %), number of prey items (N = 80 %), and importance (Ix = 75 %) than those of remaining types. The Simpson diversity index of 0.939 shows a high abundance of food prey in the wild, and the Evenness index of 0.536 suggests biased consumption of feeding selection for M. menglienica.